4x2 - 9 = 0
4x^(2)-9=0 Since -9 does not contain the variable to solve for, move it to the right-hand side of the equation by adding 9 to both sides. 4x^(2)=9 Divide each term in the equation by 4. x^(2)=(9)/(4) Take the square root of both sides of the equation to eliminate the exponent on the left-hand side. x=+-sqrt((9)/(4)) Pull all perfect square roots out from under the radical. In this case, remove the 3 because it is a perfect square. x=+-(3)/(2) First, substitute in the + portion of the \ to find the first solution. x=(3)/(2) Next, substitute in the - portion of the \ to find the second solution. x=-(3)/(2) The complete solution is the result of both the + and - portions of the solution. x=(3)/(2),-(3)/(2)
Join our real-time social learning platform and learn together with your friends!